1989
DOI: 10.1557/proc-169-703
|View full text |Cite
|
Sign up to set email alerts
|

Critical Current Density and Microstructure of Yba2Cu3O7-X Films as a Function of Film Thickness

Abstract: Thin films of nominal composition YBa 2 Cu 3 O 7 _x (YBCO) were produced on (100) SrTiO 3 substrates by coevaporation and furnace annealing. Film thicknesses in the range of 0.2 to 2.4,pm were analyzed. Microstructural investigations by cross sectional transmission electron microscopy (TEM) reveal a continuous layer of about 0.4 um thickness adjacent to the substrate with c-axis normal to the substrate plane. In thicker films the remaining top portion has the c-axis in the film plane. The critical current dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The 123 film shows a metallic behaviour at temperatures higher than 91 K, which is the onset temperature for superconductivity. Below this temperature a sharp decrease in the resistivity is observed and zero resistivity is obtained below 84 K. These results compare favourably with results given in the literature concerning ZrO2 buffer layers [9,14]. In a forthcoming publication [26] the influence of the processing parameters on the quality of the 123 film and the interracial reactions occurring in the Si/NiSiE/Zr02/123 samples will be reported.…”
Section: Electrical Propertiessupporting
confidence: 84%
See 1 more Smart Citation
“…The 123 film shows a metallic behaviour at temperatures higher than 91 K, which is the onset temperature for superconductivity. Below this temperature a sharp decrease in the resistivity is observed and zero resistivity is obtained below 84 K. These results compare favourably with results given in the literature concerning ZrO2 buffer layers [9,14]. In a forthcoming publication [26] the influence of the processing parameters on the quality of the 123 film and the interracial reactions occurring in the Si/NiSiE/Zr02/123 samples will be reported.…”
Section: Electrical Propertiessupporting
confidence: 84%
“…The most promising results are obtained with ZrO2 buffer layers on silicon substrates [9], AI20 3 substrates [13], and oxidized silicon substrates (SiO2) [14]. Supercon-ducting 123 thin films have also been prepared on MgO single crystals covered with Nb, Ag [15], or Au [16], and on SiO2 covered with Ag [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the J c decreases rapidly as the thickness of epitaxial YBCO films increases. [43][44][45][46][47][48][49] There seems to be a universal trend towards an exponential drop in J c with YBCO thickness, regardless of the deposition technique employed. For these reasons, the thickness dependence of the critical current density of YBCO films is complicated, and the optimum thickness of the superconducting layer will be different for different conditions of temperature, magnetic field and electric field, depending on the kind of application.…”
Section: Introductionmentioning
confidence: 92%
“…For these reasons, the thickness dependence of the critical current density of YBCO films is complicated, and the optimum thickness of the superconducting layer will be different for different conditions of temperature, magnetic field and electric field, depending on the kind of application. Possible causes for the drop in J c that have been reported in the literature include a transition to a-axis orientation, [43][44][45] a loss of in-plane and/or out-of-plane texture, 46,47 a decrease in the number of pinning sites, 48 and a change in the microstructure. 50 Since the HTS deposition takes place at 650-900 °C, the thermal expansion coefficients of the substrates and the HTS films have to match, or else the different contraction of HTS film and substrate on cooling to room or even cryogenic temperature will lead to mechanical stress, which can only be tolerated by the film up to a certain maximum thickness without crack formation.…”
Section: Introductionmentioning
confidence: 99%